Sagot :
Step-by-step explanation:
the equation will be like this:
√1+2x=6
first we will get the square root of 1 which is 1
1+2x=6
then the next thing we will do is to transpose 1 to the right side or we will move the constant term to the right side and the numbers with variables to the left. if we will move 1 to the right, it will become negative because it was moved through the equal sign.
2x=(-1)+6
then add the constant terms
2x=5
after that, divide it all by 2 because in order to get the value of x, we have to remove its constant term which is 2.
2x÷2=5÷2
x=5/2 or 2.5